Beginning Unix - Love, Paul; Merlino, Joe; Reed, Jeremy C.; Zimmerman, Craig; Weinstein, Paul (Wiley, 2005)
Covering all aspects of the Unix operating system and assuming no prior knowledge of Unix, this book begins with the fundamentals and works from the ground up to some of the more advanced programming techniques The authors provide a wealth of real-world experience with the Unix operating system, delivering actual examples while showing some of the common misconceptions and errors that new users make - Special emphasis is placed on the Apple Mac OS X environment as well as Linux, Solaris, and migrating from Windows to Unix A unique conversion section of the book details specific advice and instructions for transitioning Mac OS X, Windows, and Linux users